2011
DOI: 10.1016/j.psychres.2010.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Self-report and laboratory measures of impulsivity in patients with schizophrenia or schizoaffective disorder and healthy controls

Abstract: This study examined self-reported impulsivity and aggression and performance on the stop-signal task in patients with schizophrenia or schizoaffective disorder and healthy volunteers. Patients show increased stop-signal reaction time but no difference in post-error slowing, suggesting deficient inhibition but spared error monitoring. Response variability was increased in patients compared to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 31 publications
2
46
3
Order By: Relevance
“…The previous findings with schizophrenia are more mixed. Schizophrenia patients have reported higher levels of impulsivity on the BIS-11 than controls (Nolan et al, 2011), which is in the direction we found, although it was not significant in our sample. Our findings are consistent with a previous study of the BART that showed significantly less risk taking in schizophrenia patients than controls (Cheng et al, 2012).…”
contrasting
confidence: 49%
“…The previous findings with schizophrenia are more mixed. Schizophrenia patients have reported higher levels of impulsivity on the BIS-11 than controls (Nolan et al, 2011), which is in the direction we found, although it was not significant in our sample. Our findings are consistent with a previous study of the BART that showed significantly less risk taking in schizophrenia patients than controls (Cheng et al, 2012).…”
contrasting
confidence: 49%
“…A significant neurobiological mechanism underlying substance use and addiction is reduced DA function in the PFC (Koob and Volkow, 2010;Volkow et al, 2009). Deficits in PFC DA function have also been reported in schizophrenia and ADHD (Russell, 2002;Volk and Lewis, 2010), disorders that are also characterized by impulsive behaviors (American Psychiatric Association, 2000; Kaladjian et al, 2011;Nolan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that subjective (i.e., self-report) measures of self-control positively correlate with more objective (i.e., behavioral) measures of self-control (39)(40)(41). The BSC consisted of 13 items.…”
Section: Methodsmentioning
confidence: 99%